5x + 2 (x - 3) = - 2 (x - 1)

078-6--2X-2

7x - 6 = - 2x + 2

7x - 3 = - 2x - 1

Answers (1)

Know the Answer?

Not Sure About the Answer?

Get an answer to your question ✅ *“Simplify the given equation. 5x + 2 (x - 3) = - 2 (x - 1) 078-6--2X-2 7x - 6 = - 2x + 2 7x - 3 = - 2x - 1 ...”* in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.

Search for Other Answers
You Might be Interested in

The cheerleaders at Central Junior High drink orange juice after their practices. Each can contains 160 mL of juice. How many milliliters are in 2 cans?

Answers (2)

Write a doubles fact you can use to find the sum 6+5

Answers (1)

Use the Law of Sines to find the missing angle of the triangle. Find measure of angle b given that c=83, a=44 and that measure of angle a = 31. A=76.3 degrees B = 15.8 degrees C = 72.7 degrees,

Answers (1)

The ladder is 6m long and it can't touch the wall by 1.5m so how far can the ladder reach

Answers (1)

Which of the following equations is equivalent to the formula for velocity

Answers (1)

New Questions in Mathematics

Salene rolls a 1-6 number cube two times. what is the probability she will roll a 6 both times?

Answers (1)

Are the links 5 yards 12 yards and 13 yards a right triangle?

Answers (2)

A 1-unit by 3-unit rectangle is shown below. what is the area of the shaded rectangle?

Answers (1)

Write the sentence as an equation. 397 is 14 divided by d

Answers (2)

Find each missing length to the nearest tenth

Answers (1)